Meaning and Mattering: Framing Climate Change in the Documentary “A Life on our Planet” by David Attenborough - Afshan Abbas; Dr. Fauzia Janjua (University of Chitral Journal of Linguistics and Literature, 2023)
The climate crisis is a debatable issue among academics from various disciplines. The framing strategies of presenting climate change in either beneficial or destructive way play a vital role in forming the opinion of people regarding it. The present study investigates the discursive straregies of climate change framing in the genre of documentary from the perspective of ecolinguistics. For the said purpose, the climate change documentary (A Life on our planet released on 2020) is chosen to analyse the framing techniques employed by the narrator David Attenborough for the portrayal of climate change. In order to analyse frames, the mixed methods approach is used to identify the trigger words used as frames. The findings show that climate change is significantly portrayed in three important eco centric frames: nuclear fatalism as an environmental catastrophe, diversity into decline and nature as a buried treasure. Keywords: climate change, ecolinguistics, framing, documentary, trigger words